Micro-Valences: Perceiving Affective Valence in Everyday Objects - Lebrecht, Sophie; Bar, Moshe; Barrett, Lisa F.; Tarr, Michael J. (Frontiers in Psychology, 2012)
Perceiving the affective valence of objects influences how we think about and react to the world around us. Conversely, the speed and quality with which we visually recognize objects in a visual scene can vary dramatically depending on that scene’s affective content. Although typical visual scenes contain mostly “everyday” objects, the affect perception in visual objects has been studied using somewhat atypical stimuli with strong affective valences (e.g., guns or roses). Here we explore whether affective valence must be strong or overt to exert an effect on our visual perception. We conclude that everyday objects carry subtle affective valences – “micro-valences” – which are intrinsic to their perceptual representation.